A design and optimization framework of variable-density lattice structures for additive manufacturing. Issue 26 (26th October 2022) - Al Khalil, Monzer; Lebaal, Nadhir; Demoly, Frédéric; Roth, Sebastien
Abstract: With the development of additive manufacturing (AM), research interest is currently focused on lattice structures development due to their interesting mechanical properties. It implies the opportunity at the engineering level to be able to specify – beyond the shapes – mechanical properties distributed in the space to be manufactured. The article aims at introducing a design and optimization framework for AM, which highlights variable-density lattice structures. By processing both a topology optimization within a rough design space and a design of experiments driven parametric optimization, the development process of suitable and specific strength structures for AM becomes seamless and efficient.